Synthesis and Characterization of Copper Nanoparticles with Bioreductor Carica Dieng (Carica pubescens) Seed Extract - Setiani, Fifin; Suyatno, Suyatno (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Secondary metabolite compounds in plants act as bioreductors in the metal reduction process and complement inorganic reductants. This study studied the characteristics of copper nanoparticles using Carica Dieng (Carica pubescens) seed extract. The synthesis of copper nanoparticles was carried out using the green synthesis method by reducing CuSO4 10 mM with distilled water extract from Carica Dieng (Carica pubescens) seeds. The Synthesis was carried out with the ratio of the composition of the extract and CuSO4 solution 1:3 at pH 10. Nanoparticles were then characterized using UV-Vis spectrophotometer and PSA (Particle Size Analyzer) instruments. The characterization results using a UV-Vis Spectrophotometer showed a maximum absorption peak at a wavelength of 535 nm; the wavelength is included in the wavelength range of copper nanoparticles, which ranges from 500-700 nm. The particle size distribution analyzed using PSA shows an average size of 14.49 nm; this size is included in the range of nanoparticle sizes, which is between 1-100 nm, thus proving that nanoparticles have been successfully formed, the Poly Dispersity Index (PDI) value obtained is 0.1943 which indicates that the nanoparticle sample is categorized as homogeneous so that it has uniform size uniformity.